Dinamika Triangular : Analisis Bibliometrik Corporate Social Responsibility, Political Connections, dan Sustainability - Wydha Mustika Maharani; Dhiptya Ratri Anggraheni (Public Service and Governance Journal, 2025)
This study presents a bibliometric analysis of the dynamic relationship between Corporate Social Responsibility (CSR), political connections, and sustainability. CSR has evolved from philanthropy to an important business strategy, driven by consumer demands and government regulations. Political connections influence the implementation of CSR, either facilitating or hindering it, depending on a country's governance system. Sustainability, measured by ESG pillars, is essential for competitiveness and long-term performance. Using the PRISMA and VOSviewer methodologies, 87 documents from Scopus were analyzed, revealing a significant increase in publications since 2019, with China and Indonesia as the main contributors. These findings identify 23 topic clusters, highlighting government interventions, green innovation, and sustainability reporting in enhancing CSR performance and corporate sustainability. This research provides significant theoretical and practical contributions to the CSR literature.